CRÍTICOS & CRITICADOS A CRÍTICA CINEMATOGRÁFICA E SUA RELAÇÃO COM OS CINEASTAS DA RETOMADA - Manso, Franthiesco Anthonio Ballerini (2008)
The paper objects to analyze the film critic during the period known as the restart (Retomada) of the national cinema. It was chosen the major vehicles in terms of circulation in the southeast region of Brazil, the newspapers O Globo (Rio de Janeiro), Folha de S.Paulo e O Estado de S.Paulo (São Paulo) and the weekly magazine Veja, in order to make a content analysis of the six biggest box office of the restart period and, after that, check the reception of them by their directors, by semi-structured interviews. The intention is to analyze which conflicts exists in the relation between the film critics and the directors, in order to contribute to a better understanding of those very important elements of the film industry. The confront of the analysis material with the interviews confirmed the hypothesis of the existence of conflicts of values and opinions between both sides and permitted to identify pre-judgments, sympathies and antipathies, emotional and non-based analysis of some film critics and directors, but also based thoughts of others, showing a rich diversity that doesn t fit into just one definition.(AU)